Application of Surfactant for Enhancing the Adsorption of Azo Dye Onto Buckthorn Tree Wood Surface - Edan Al-Mammar, Dunya; Abbas Mohammed, Rawaa (Iraqi Journal of Science, 2021)
Cetyl trimethyl ammonium bromide (CTAB), was used as surfactant to enhancethe removal of Congo- red (C-R) dye from its solution by employing a wood ofbuckthorn tree as a low cost and eco-friendly adsorbent. Different factors affectingthe sorption process like, time of adsorption, wood dose, initial (C-R) concentrationand hydrogen ion concentration have been studied for both adsorbent wood (W) andmodified wood (MW). The suitability of the two isotherm models Langmuir andfrundlich to the equilibrium results was mentioned for the adsorption of (C-R) onboth wood and modified wood. From the value of correlation - factor, frundlichmodel give a better fit than Langmuir isotherm model. Thermodynamic functionsuch as the changes in enthalpy ΔH°, entropy ΔSo and Gibes free energy ΔGo for theadsorption process was guessed. These values illustrate that physi-sorption takeplace .The negative values of ΔHo shows that the adsorption process accompanywith heat releasing with decreasing the randomness of the (solid-solution) interface.Furthermore the negative values of ΔG° indicated that adsorption of (C-R) dye ontothe wood and modified wood occurs spontaneously.